PENGARUH VISUM ET REPERTUM DALAM MENGUNGKAP TINDAK PIDANA PENGANIAYAAN - Siregar, Dahris (Rechtsregel : Jurnal Ilmu Hukum, 2024)
Evidence is needed in cases of ordinary and severe investigative persecution. Law No. 8 of 1981 regulates the intended evidence. The court usually asks the defendant or suspect to explain his actions to the victim when proving the attempted goods. However, in reality, all those who are unlikely to commit crimes are brought to justice, including human beings, whether it is life or death. Proof of letters requested with the help of a doctor as an expert is one of the most important evidences in situations of persecution with visum et repertum, the medical results examined can be documented in writing in the form of a certificate, as well as an expert witness as a doctor. This research method is normative research, the meaning of law is considered either as mentioned in law books or as a standard that is a standard for the behavior of people who are considered reasonable. If visum et repertum does not align using the data provided by the defendant, the statement may be revoked, and visum et repertum has the ability to be examined again if the defendant does give a false confession